Effects of prostaglandin E(2) on the subcellular localization of Epac-1 and Rap1 proteins during Fcγ receptor mediated phagocytosis in alveolar macrophages - Brock, Thomas G. (2007)
Recent studies have demonstrated a central role for the exchange protein activated by cAMP (Epac) in the inhibition of Fcγ-receptor mediated phagocytosis and bacterial killing by prostaglandin E(2) (PGE(2)) in macrophages. However, the subcellular localization of Epac, and its primary target Rap1, has yet to be determined in primary macrophages. Therefore, we used immunofluorescent techniques and phagosome isolation to localize Epac-1 and Rap1 in alveolar macrophages. Epac-1 was predominantly expressed on punctate and tubular membranes throughout the cell body; on the plasma membrane; and co-localized with microtubule organizing centers (MTOCs). Rap1 was abundant on punctate membranes, less abundant on plasma membrane, and also found on MTOCs. Following PGE(2) treatment, Epac-1, but not Rap1, accumulated on the nuclear envelope and disappeared from MTOCs. By immunofluorescent microscopy, both Epac-1 and Rap1 were seen to associate with phagosomes containing IgG-opsonized beads, but this association appeared weak, as we failed to observe such interactions in phagosomes isolated from cells at various timepoints after bead ingestion. Strikingly, however, Epac-1, but not Rap1, appeared to accumulate on maturing phagosomes, but only after PGE(2) treatment (or treatment with a selective Epac-1 agonist). This association was confirmed in isolated phagosome preparations. The changes in Epac-1 localization were too slow to account for the inhibitory effects of PGE(2) on phagocytosis. However, the appearance of Epac-1 on late phagosomes following PGE(2) treatment might be important for suppressing H(2)O(2) production and inhibiting the killing of intraphagosomal pathogens. The absence of Rap1 on late phagosomes suggests that the effect of Epac-1 might not require Rap1.